Arsenic Speciation of Solvent-Extracted Leachate from New and Weathered CCA-Treated Wood - KHAN, BERNINE I. (2004)
For the past 60 yr, chromate-copper-arsenate (CCA) has been used to pressure-treat millions of cubic meters of wood in the United States for the construction of many outdoor structures. Leaching of arsenic from these structures is a possible health concern as there exists the potential for soil and groundwater contamination. While previous studies have focused on total arsenic concentrations leaching from CCA-treated wood, information pertaining to the speciation of arsenic leached is limited. Since arsenic toxicity is dependent upon speciation, the objective of this study was to identify and quantify arsenic species leaching from new and weathered CCA-treated wood and CCA-treated wood ash. Solvent-extraction experiments were carried out by subjecting the treated wood and the ash to solvents of varying pH values, solvents defined in the EPA’s Synthetic Precipitation Leaching Procedure (SPLP) and Toxicity Characteristic Leaching Procedure (TCLP), rainwater, deionized water, and seawater. The generated leachates were analyzed for inorganic As(III) and As(V) and the organoarsenic species, monomethylarsonic acid (MMAA) and dimethylarsinic acid (DMAA), using high-performance liquid chromatography followed by hydride generation and atomic fluorescence spectrometry (HPLC–HG-AFS). Only the inorganic species were detected in any of the wood leachates; no organoarsenic species were found. Inorganic As(V) was the major detectable species leaching from both new and weathered wood. The weathered wood leached relatively more overall arsenic and was attributed to increased inorganic As(III) leaching. The greater presence of As(III) in the weathered wood samples as compared to the new wood samples may be due to natural chemical and biological transformations during the weathering process. CCA-treated wood ash leached more arsenic than unburned wood using the SPLP and TCLP, and ash samples leached more inorganic As(III) than the unburned counterparts. Increased leaching was due to higher concentrations of arsenic within the ash and to the conversion of some As(V) to As(III) during combustion.